Shifting partisan public opinion towards Community Choice Aggregation through outreach and awareness. - Victor Y Wu; Richard Howarth (PLoS ONE, 2023)
Community Choice Aggregation (CCA) is a rapidly expanding electricity supply model in the United States. By enabling local governments to obtain electricity for their residents, CCAs have the potential to increase the use of renewable energy while lowering costs. Recent studies have focused on how CCAs will impact renewable energy markets, since at least five more states are currently considering CCA-enabling legislation. However, little research has been done on partisan attitudes towards CCAs or how to shift public opinion to support the continued expansion of CCAs. We use a nationally representative survey experiment of 1,862 respondents to evaluate outreach and awareness campaigns by nonprofit and government organizations seeking to expand CCAs. We find that most Americans are currently unfamiliar with CCAs, but exposing them to educational outreach information increases their support for CCAs at the state, local, and personal levels. Furthermore, this information is equally effective at increasing support among both Democrats and Republicans, despite partisan polarization on renewable energy. However, this information did not significantly affect respondents' price sensitivity with regard to CCAs. Our results suggest that outreach and awareness campaigns can be effective at increasing support for CCA among both Democrats and Republicans.